The Art of Community: Building the New Age of Participation - Bacon, Jono (O'Reilly Media, 2012)
Online communities provide a wide range of opportunities for supporting a cause, marketing a product or service, or building open source software. The Art of Community helps you recruit members, motivate them, and manage them as active participants. Author Jono Bacon offers experiences and observations from his 14-year effort to build and manage communities, including his current position as manager for Ubuntu.Discover how your community can become a reliable support network, a valuable source of new ideas, and a powerful marketing force. This expanded edition shows you how to keep community projects on track, make use of social media, and organize collaborative events. Interviews with 12 community management leaders, including Linus Torvalds, Tim O’Reilly, and Mike Shinoda, provide useful insights.Develop specific objectives and goals for building your communityBuild processes to help contributors perform tasks, work together, and share successesProvide tools and infrastructure that enable members to work quicklyCreate buzz around your community to get more people involvedHarness social media to broadcast information, collaborate, and get feedbackUse several techniques to track progress on community goalsIdentify and manage conflict, such as dealing with divisive personalities

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

Agile Project Management For Dummies - Layton, Mark C. (John Wiley & Sons, 2012)
Be flexible and faster with Agile project management As mobile and web technologies continue to evolve rapidly, there is added pressure to develop and implement software projects in weeks instead of months. Agile Project Management For Dummies can make that happen. This is the first book to provide a simple, step–by–step guide to Agile Project Management approaches, tools, and techniques. With the fast pace of mobile and web technology development, software project development must keep pace; Agile Project Management enables developers to complete and implement projects more quickly and this book shows you how. Offers a practical context for understanding and applying Agile techniques, moving from theory into actual practice Explains when to use Agile and how to avoid common pitfalls Written by experts who know how to apply the principles in real–world situations Agile Project Management For Dummies enables you to understand and apply Agile principles for faster, more accurate development.

Adaptability: the art of winning in an age of uncertainty - McKeown, Max (Kogan Page, 2012)
Keywords: Adaptability (Psychology); Success

Adapt: Why Success Always Starts with Failure - Harford, Tim (Abacus, 2012)
Everything we know about solving the world's problems is wrong. Out: Plans, experts and above all, leaders. In: Adapting - improvise rather than plan; fail, learn, and try againIn this groundbreaking new book, Tim Harford shows how the world's most complex and important problems - including terrorism, climate change, poverty, innovation, and the financial crisis - can only be solved from the bottom up by rapid experimenting and adapting.From a spaceport in the Mojave Desert to the street battles of Iraq, from a blazing offshore drilling rig to everyday decisions in our business and personal lives, this is a handbook for surviving - and prospering - in our complex and ever-shifting world.